A Review of Advanced Flexible Lithium‐Ion Batteries. Issue 9 (24th March 2018) - Tao, Tao; Lu, Shengguo; Chen, Ying
Abstract: The rapid development of flexible electronics has triggered extensive efforts to explore matching flexible energy‐storage devices as power sources. Flexible lithium‐ion batteries (LIBs) have been demonstrated as the current most attractive and versatile energy storage devices for flexible electronics. A series of designs and constructions for flexible LIBs have been investigated in recent years. Particularly, significant progress has been achieved in finding high performance electrolyte and electrode materials, new structural designs, as well as suitable fabrication methods for flexible LIBs. In this review, the recent advances in the exploration of flexible lithium‐ion batteries are summarized and discussed, with special focus on the selectivity of flexible electrode/electrolyte materials, cell structure design, and full cell assembly process. Perspectives for the future development of flexible LIBs are also discussed. Abstract : Flexible lithium‐ion batteries (LIBs) have been regarded as the most effective and versatile energy storage devices for flexible electronics . In this review, a series of designs and constructions for flexible LIBs are summarized. Particularly, significant progress in flexible electrode/electrolyte materials selectivity, cell structural design, and full cell assembly is presented.